2013
DOI: 10.1289/ehp.1205783
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Thyroid Function among Belarusian Children and Adolescents Exposed to Iodine-131 from the Accident at the Chernobyl Nuclear Plant

Abstract: Background: Thyroid dysfunction after exposure to low or moderate doses of radioactive iodine-131 (131I) at a young age is a public health concern. However, quantitative data are sparse concerning 131I-related risk of these common diseases.Objective: Our goal was to assess the prevalence of thyroid dysfunction in association with 131I exposure during childhood (≤ 18 years) due to fallout from the Chernobyl accident.Methods: We conducted a cross-sectional analysis of hypothyroidism, hyperthyroidism, autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 41 publications
3
46
1
Order By: Relevance
“…Contrasting with the evident correlation between childhood radiation exposure and an increase in thyroid cancer incidence, the effects of radiation on thyroid status are less clear. Belarusian and Ukrainian cohort studies suggested that an increase in serum TSH levels was related to childhood exposure to 131 I [8,9], while other studies did not suggest any relationship [10,11]. In rodent models, an early study demonstrated that whole body or cervical X-irradiation could change serum thyroid hormone levels in adult rats [12].…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting with the evident correlation between childhood radiation exposure and an increase in thyroid cancer incidence, the effects of radiation on thyroid status are less clear. Belarusian and Ukrainian cohort studies suggested that an increase in serum TSH levels was related to childhood exposure to 131 I [8,9], while other studies did not suggest any relationship [10,11]. In rodent models, an early study demonstrated that whole body or cervical X-irradiation could change serum thyroid hormone levels in adult rats [12].…”
Section: Discussionmentioning
confidence: 99%
“…We examined the reliability of responses to questions about residential history and dietary pattern in the distant past obtained for a cohort of 11,732 subjects of a long-term epidemiological study of thyroid cancer and other thyroid disease in individuals exposed in childhood and adolescence to radiation following the Chernobyl accident, which occurred on 26 April 1986 (Stezhko et al 2004; Zablotska et al 2011; Ostroumova et al 2013). The majority of the study subjects or his/her relatives were interviewed at least two times between 1996 and 2007 during two medical screenings of the cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. National Cancer Institute, in collaboration with the Belarusian Ministry of Health, has been conducting a study of thyroid cancer and other thyroid diseases in a cohort of 11,732 persons who were exposed in childhood and adolescence to fallout from the Chernobyl accident that occurred on April 26, 1986 (1012). To evaluate the radiation risk of thyroid diseases, deterministic thyroid doses were reconstructed for the study subjects based on estimated 131 I activity in the thyroid derived from direct thyroid measurements of each cohort member and responses to interviews of all subjects on residential history, consumption of milk, milk products and leafy vegetables and administration of stable iodine (13).…”
Section: Introductionmentioning
confidence: 99%